2011
DOI: 10.1097/aog.0b013e3182289eab
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pack Supply on Oral Contraceptive Pill Continuation

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 14 publications
1
38
1
Order By: Relevance
“…Unfortunately most warning notes on the pill packages do not address or acknowledge about mood changes adequately while this is an important issue for ensuring that women will continue to use pills in order to prevent at least unwanted pregnancies [16,17]. In fact, discontinuity of oral contraceptive pills might jeopardize women’s health in general and reproductive health in particular [18,19]. A study from the USA found that 33% of oral contraceptive pills users discontinued using pills 6 months after the start due its side effects and 33% of these side effects were emotional and behavioral [4].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately most warning notes on the pill packages do not address or acknowledge about mood changes adequately while this is an important issue for ensuring that women will continue to use pills in order to prevent at least unwanted pregnancies [16,17]. In fact, discontinuity of oral contraceptive pills might jeopardize women’s health in general and reproductive health in particular [18,19]. A study from the USA found that 33% of oral contraceptive pills users discontinued using pills 6 months after the start due its side effects and 33% of these side effects were emotional and behavioral [4].…”
Section: Discussionmentioning
confidence: 99%
“…The methods and results of the larger study are reported elsewhere [41]. Columbia University Institutional Review Board approved this research.…”
Section: Methodsmentioning
confidence: 99%
“…46 White and Westhoff conducted a randomized trial in which they compared supplying three versus seven packs. 47 They found that the odds of continuing OCPs at 6 months were 60% higher among young adult women who received the longer supply. The impact of the longer supply was more pronounced among women younger than 18 years, who were sevenfold more likely to continue at 6 months.…”
Section: Pack Supplymentioning
confidence: 99%